LITERASI EKOLOGIS LITERASI EKOLOGIS: Implementasi Pendidikan Lingkungan Hidup bagi Siswa SMP Negeri Se-Distrik Sentani - Labobar, Julianus; Kapojos, Sintia (Universitas Veteran Bangun Nusantara, 2023)
This research investigates the implementation of environmental education in Public Junior High Schools across the Sentani District and its impact on students' understanding of environmental issues and their ecological literacy. The study identifies several challenges, including a lack of ecological knowledge among students and limited training for teachers in delivering environmental education. Qualitative methodology was employed, utilizing in-depth interviews, direct observations, and documentary analysis. The research findings indicate that the implementation of environmental education through integration into the school curriculum across various subjects and school activities plays a crucial role in shaping ecological literacy and students' environmental awareness. Teachers who can relate the learning materials to the local context of students have a positive influence on students' understanding of environmental issues. Nevertheless, challenges such as the availability of resources and inadequate teacher training remain obstacles. The integration of environmental education yields positive results, with students beginning to appreciate nature, feeling responsible for the environment, and demonstrating critical thinking regarding the consequences of their actions. In conclusion, this research underscores the significant roles of environmental education and ecological literacy in shaping students' attitudes, knowledge, and behaviors related to the environment. The implementation of environmental education in schools can provide substantial benefits in producing a generation that is more environmentally conscious and capable of taking action to preserve environmental sustainability.